Intakes of magnesium, calcium and risk of fatty liver disease and prediabetes - Li, Wenshuai; Zhu, Xiangzhu; Song, Yiqing; Fan, Lei; Wu, Lijun; Kabagambe, Edmond K; Hou, Lifang; Shrubsole, Martha J; Liu, Jie; Dai, Qi (Public health nutrition, 2018)
Obesity and insulin resistance play important roles in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Mg intake is linked to a reduced risk of metabolic syndrome and insulin resistance; people with NAFLD or alcoholic liver disease are at high risk of Mg deficiency. The present study aimed to investigate whether Mg and Ca intakes were associated with risk of fatty liver disease and prediabetes by alcohol drinking status. We analysed the association between Ca or Mg intake and fatty liver disease, prediabetes or both prediabetes and fatty liver disease in cross-sectional analyses. Third National Health and Nutrition Examination Survey (NHANES III) follow-up cohort of US adults. Nationally representative sample of US adults in NHANES (n 13 489). After adjusting for potential confounders, Mg intake was associated with approximately 30 % reduced odds of fatty liver disease and prediabetes, comparing the highest intake quartile v. the lowest. Mg intake may only be related to reduced odds of fatty liver disease and prediabetes in those whose Ca intake is less than 1200 mg/d. Mg intake may also only be associated with reduced odds of fatty liver disease among alcohol drinkers. The study suggests that high intake of Mg may be associated with reduced risks of fatty liver disease and prediabetes. Further large studies, particularly prospective cohort studies, are warranted to confirm the findings.